Pengaruh Budaya Organisasi dan Kepemimpinan Terhadap Kinerja Karyawan pada PT. Bank Perkreditan Rakyat (BPR) X Koto Singkarak - Muhammad Firdo; Netti Indrawati; Afrimasri Afrimasri (Jurnal Publikasi Ilmu Manajemen, 2023)
. This study discusses "The Influence of Organizational Culture and Leadership on Employee Performance at PT. People's Credit Bank (BPR) X Koto Singkarak". level of education, status and length of work.In this study the authors gave or distributed 31 files of questionnaires. For the Organizational Culture variable (X1) the t-count value is 2.999 with a significance level of 0.006. Because the calculated t value is greater than t table 2.909 > 2.048 and the significance level value is 0.007 <0.05 then H1 is accepted and Ho is accepted. This proves that Organizational Culture has a significant effect on Employee Performance at PT. People's Credit Bank (BPR) X Koto Singkarak. For the Organizational Culture variable (X2) the t-count value is 3.983 with a significance level of 0.000. Because the t-count value is greater than t-table 3.983 > 2.048 and the significant level value is 0.000 <0.05 then H2 is accepted and Ho is accepted. This proves that Leadership (X.1) has a significant effect on Employee Performance at PT. People's Credit Bank (BPR) X Koto Singkarak. The hypothesis is accepted if fcount > f table and sig value < a 0.05 from table 3.30, it can be seen that fcount 13.056 > from f table 3.30 with a significance value of 0.000 <0.05 then Ho is accepted H1 is accepted this indicates that the independent variable has a significant and simultaneous influence simultaneously on the dependent variable.